Geschichte des Küstenverlaufs im Stadtgebiet von Cádiz - Arteaga Matute, Oswaldo; Kölling, Annette; Kölling, Martin; Roos, Anna-Maria; Schulz, Helga (Madrider Mitteilungen, 2020)
Deutsche Zusammenfassung folgt.